The Effect of College Students' Adaptability on Nomophobia: Based on Lasso Regression - Luo, Jing; Ren, Shixiu; Li, Yuxin; Liu, Tour (Frontiers in Psychiatry, 2021)
Smartphones can improve our lives, but also consume our lives. It is known that problematic mobile phone use, such as nomophobia, can lead to some mental health problems. So far, psychological factors behind nomophobia were yet to be fully discovered. Previous studies showed that individuals' adaptability was closely related to nomophobia. However, adaptability was a complex construct that contains various components, and it was unclear whether these components contributed equally to nomophobia. This study investigated 678 college students by using Chinese versions of the nomophobia questionnaire, mobile phone addiction tendency scale, and freshmen adaptability scale. Lasso regression was used to further explore the key factors that could affect nomophobia. Model results showed that the value of λ+1se was [0.303, 0.423] at the minimum mean squared error in the training data. Emotional adaptability significantly predicted the fear of being unable to access information (β = −0.022, p < 0.001), losing convenience (β = −0.067, p < 0.001), and losing Internet connection (β = −0.003, p < 0.01) after λ+1se was included in the testing data, and the R2 were 0.496, 0.483, and 0.493. Homesickness adaptability significantly predicted the fear of losing contact (β = −0.056, p < 0.05), and R2 was 0.508. In addition, similar results were obtained by using datasets of mobile phone addiction and adaptability. Therefore, we concluded that the emotional adaptability has an important effect on nomophobia. Additionally, we also found that homesickness adaptability has an important role in predicting fear of losing contact.